The art of not making the new artist-artisan relationship - Petry, Michael (London Thames & Hudson, 2011)
Can an artist claim that an object is a work of art if it has been made for him or her by someone else? If so, who is the author of such a work? And just what is the difference between a work of art and a work of craft? In the first book of its kind, Michael Petry tackles these questions head on.
When art meets craft -- Glass -- Metal -- Stone -- Textiles -- Other materials -- Interviews.
Includes list of artists' websites (p. 201).
Includes bibliographical references (p. 198-200) and index.
Keywords: Art -- Philosophy; Handicraft -- Philosophy; Decorative arts -- Philosophy; Handicraft in art; Creation (Literary, artistic, etc.); Found objects (Art)